Stability Threshold of Herringbone Grooved Aerodynamic Journal Bearings with External Stiffness and Damping Elements - Jun TOMIOKA; Norifumi MIYANAGA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2013)
Herringbone grooved aerodynamic journal bearings have better stability characteristics than plane aerodynamic journal bearings. In addition, the use of flexibly supported bearings is one of the efficient way to improve the bearing stability. Therefore, the combination bearing systems have prospects of realization of ultra-high-speed operations. The purpose of this work is to evaluate the effect of external stiffness and damping elements on the bearing stability. The Voigt rheological model was used for the external elements, in which the stiffness and the damping were treated as the linear elements. It was clarified that the stability boundary of the herringbone grooved aerodynamic journal bearings supported by suitable stiffness and damping elements can be heightened more than three times compared with the rigidly supported bearings.